PHRASEOLOGISMS WITH NUMERICAL COMPONENTS IN UKRAINIAN, ENGLISH AND CHINESE - Danylenko, Yuliya (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
Abstract. The relevance of the article is due to the need to deepen the integration of various achievements of the Ukrainian language and culture into the global cultural fund. The purpose of the article is to study the verbalization of the language universal “all” on the basis of phraseological units with numerical components hundred, thousand, ten thousand, one million on the material of Ukrainian, English and Chinese languages. The following tasks are set: 1) consideration of the category of quantity as a component of the language universal “all”; 2) definition of lingual and extralingual components of the quantity category; 3) selection and classification of phraseological units with numerical components hundred, thousand, ten thousand, one million in Ukrainian, English and Chinese; 4) implementation of linguistic and comparative analysis of phraseological units; 5) systematization and generalization of the results obtained to clarify and deepen the content of the language universal “all”. In the research process, a comparative method, a descriptive method, a component analysis method, and an interpretation method were used. Operating with lingual and extralingual facts, their transformation and combination becomes the basis for further conceptualization of generally valid concepts in the linguistic picture of the world. The category of linguistic quantity in the article is considered as a component of the linguistic universal “all”. The results of a comparative analysis of idiomatic expressions with numerical components in three languages enable to partially detail and deepen the content of the universal “all”.An important place in the cultural system is occupied by the symbolism of numbers: Western, Slavic and Eastern cultural traditions have their own characteristic features. In Chinese culture, one of the representatives of the meaning of completeness is the number ten thousand. In Ukrainian, among phraseological units with the above-mentioned numerical components, the most frequent component is hundred. Further study of the representation of numbers in Ukrainian, English and Chinese allows us to find out some of the philological, historical, cultural features of the speakers of these languages.